STUDI PENINGKATAN EFISIENSI PENGOPERASIAN TURBIN GAS PEMBANGKIT LISTRIK PT CPI - (NIM 28196033), AZHAR
Abstract : PT CPI is currently operating 21 units of Gas Turbine Generator to generate electric power required for its operation in exploring and producing crude oil. Current gas turbine generator operation practice is to determine number of units to be put in operation in order to meet the daily highest electrical load which takes place at the high ambient temperature of a day. Current practice does not include procedure to distribute load among gas turbine generator units when load is low while generating capability of turbines is high which occurs at low ambient temperature of a day to optimize fuel consumption. In general, about 60 % of electric power generation cost derives from fuel cost. Therefore efforts to optimize fuel consumption is required to improve gas turbine generator operation efficiency. Gas turbine performance curve indicates that fuel consumption is quadratic function of output (load). Based on this condition, it is proposed to utilize quadratic programming to determine distribution of load among gas turbine units with the purpose to optimize fuel consumption. The constraints are total load to be met, maximum and minimum output of each gas turbine unit, and non negative characteristic of output. The study indicates that load distribution among gas turbine units by shutting down some units when load is low while generating capability of turbines is high at low ambien temperature of a day, and putting them back in operation as load increases while generating capability decreases at high ambien temperature of a day can save fuel consumption by 1.8 % or equivalent to US $ 1,692,585.00 per year. Saving in fuel consumption will improve power generation cost which in turn will contribute to company overall cost efficiency.